First Japanese records of crosses between Whistling Cygnus columbianus columbianus and Bewick's Swans C. c. bewickii - Mikami, Shiro (Wildfowl, 1989)
'Crossed' families of Bewick's and Whistling Swans were observed four times. Three of four were between 'Darky' Bewick's and Whistling Swans and the other between a 'Yellowneb' Bewick's and a Whistling Swan. The bill patterns of juveniles varied but were intermediate types of the two subspecies.